Impact of artificial intelligence-enabled service attributes on customer satisfaction and loyalty in chain hotels: Evidence from coastal tourism destinations in western Thailand - Noptanit Chotisarn; Thadathibesra Phuthong (Social Sciences and Humanities Open)
This study investigates how artificial intelligence (AI)-enabled service attributes affect customer satisfaction and loyalty in chain hotels located in coastal tourism destinations in Western Thailand. We integrate the technology acceptance model, SERVQUAL, the stimulus-organism-response model, and the humanness-value-loyalty model to examine how factors like reliability, perceived intelligence, service efficiency, aesthetics, and enjoyment affect satisfaction with AI-based customer services and customer loyalty. Data from 186 hotel guests were analyzed using partial least squares structural equation modeling. The results reveal that service efficiency (β = 0.251, p < 0.01) and enjoyment (β = 0.526, p < 0.001) significantly influence satisfaction with AI-based services. Additionally, satisfaction strongly affected customer loyalty (β = 0.833, p < 0.001); however, reliability, perceived intelligence, and aesthetics did not significantly influence satisfaction. The model demonstrates strong explanatory power, with R2 values of 0.765 for satisfaction and 0.694 for loyalty. Mediation analysis shows that satisfaction significantly mediates the relationships between enjoyment and loyalty and between service efficiency and loyalty. These findings provide valuable insights for hotel managers implementing AI technologies, emphasizing the importance of creating efficient and enjoyable AI interactions to enhance customer satisfaction and foster long-term loyalty. This study contributes to the growing literature on AI in hospitality by comprehensively elucidating how AI-enabled service attributes influence customer outcomes in a specific market context.